On the shear failure of incipient rock discontinuities under CNL and CNS boundary conditions : insights from DEM modelling - Shang, Junlong (2020)
This paper presents a numerical investigation of the effects of boundary conditions, i.e., constant normal load (CNL) and constant normal stiffness (CNS), on the failure mechanism of incipient rock discontinuities in direct shear. A series of numerical simulations were performed using the particle-based discrete element method (DEM), in which rock matrix and rock bridges (on incipient joint planes) were modeled as an assembly of rigid particles that were bonded together at their contacts. Smooth-joint model was assigned to particles of the persistent portions of incipient rock joints. Input micro-parameters of particles, bonds and smooth-joint were calibrated against a series of laboratory experiments. The study reveals that CNL and CNS boundary conditions significantly affect shear characteristics of incipient rock discontinuities. Peak shear stress increased significantly (up to three times) in the CNS direct shear in comparison with that measured in the CNL direct shear under the same initially applied normal stresses. The significant increase of shear stress in the CNS direct shear tests conducted in this study was related to the opening of newly created micro-cracks and creation of the rupture zones within the rock bridges, leading to a dramatic increase in the normal stresses. In the meanwhile, yield behavior was observed in the CNS direct shear while brittle failure was noticed in the CNL direct shear. It is also found that micro-cracks initiated at the vicinity of rock bridges in both CNL and CNS shear tests, while they propagated differently due to the gradual increase of normal stress under CNS boundary conditions.